Equi–size nesting of Platonic and Archimedean metal–organic polyhedra into a twin capsid - Hongmei Gan (Nature Portfolio, 2020)
Supramolecular constructs that mimic complex biological assemblies are synthetically challenging. Here, the authors present a double-shell cage wherein two independent metal-organic polyhedra are nested together in a manner analogous to that found in double-shell virus capsids.